APPLICATION OF PROTECTIVE COATINGS TO IMPROVE OPERATIONAL CHARACTERISTICS OF THE VESSELS - I. M. Abacharaev; M. M. Abacharaev (Вестник Дагестанского государственного технического университета: Технические науки)
This article outlines the results of analytical and experimental research of authors under the decision of problems of increase of service life of components of ships (propellers) details of their machines and mechanisms (axis, fingers, hydraulic pumps, cylinder liners of diesel engines)subject to intensive cavitation erosion and wear.A new option cavitation resistance, including structural, physical, mechanical, electrochemical properties of materials and coatings. The novelty criterion is that when using it creates the possibility of a priori determination of the composition and structure kavitatsionnogo material coverage for specific components of ships, the details of their machines and mechanisms. The advantage of the new parameter cavitation resistance of the authors in the fact that it allows you to calculate the period (resource) warranty details in the conditions of influence of cavitation. This is a pioneer in the world practice. On the basis of new theoretical positions of the authors developed compositions diffusion and plasma kavitatsionnogo coatings.